The Role of Metabolic Enzymes in the Regulation of Inflammation - Godfrey, Wesley H. (Metabolites, 2020)
Immune cells undergo dramatic metabolic reprogramming in response to external stimuli. These metabolic pathways, long considered as simple housekeeping functions, are increasingly understood to critically regulate the immune response, determining the activation, differentiation, and downstream effector functions of both lymphoid and myeloid cells. Within the complex metabolic networks associated with immune activation, several enzymes play key roles in regulating inflammation and represent potential therapeutic targets in human disease. In some cases, these enzymes control flux through pathways required to meet specific energetic or metabolic demands of the immune response. In other cases, key enzymes control the concentrations of immunoactive metabolites with direct roles in signaling. Finally, and perhaps most interestingly, several metabolic enzymes have evolved moonlighting functions, with roles in the immune response that are entirely independent of their conventional enzyme activities. Here, we review key metabolic enzymes that critically regulate inflammation, highlighting mechanistic insights and opportunities for clinical intervention.